Effectiveness of fertilization system in forming the productivity of sunflower plant (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The results of two years of research on the effect of combining different options for pre-sowing, sowing, and root fertilization on the formation of plant productivity elements and the biological yield of seeds of the high-oleic, mid-season sunflower hybrid SY Fenomeno are presented.Formulation of the problem. The problem concerning the specifics of sunflower nutrition is important for determining the theoretical basis for algorithms for the application of various types of fertilizers that will ensure a higher level of realization of the biological productivity potential of this crop. Despite a significant amount of research in this area, a number of issues, primarily regarding a comprehensive approach to fertilezer application, remain unresolved, which determined the direction of the research conducted.The purpose of the research was to evaluate the elements of plant productivity and biological seed yield of the high-oleic, mid-season sunflower hybrid SY Fenomeno depending on the application of various combinations of pre-sowing, sowing and root mineral fertilizers in the conditions of the Left-Bank Forest-Steppe of Ukraine.Research methods. The study was conducted in 2024 and 2025 at the «Gryga» Farm in the Poltava district of the Poltava region. A two-factor field experiment was set up using the split-plot method in three replicates. The first-order plots were four variants of root feeding of crops with UAN32 in phases V5 and V6: 1 – control (no feeding); 2 – UAN32 at a dose of 65 kg/ha (N20); 3 – UAN32 at a dose of 95 kg/ha (N30); 4 – UAN32 at a dose of 125 kg/ha (N40). The second-order plots were five options for combining pre-sowing and post-sowing application of complex fertilizers: I – absolute control (no fertilizers); II – pre-sowing application of ammonium sulfate at a dose of 100 kg/ha (N21S24) in combination with top dressing application of ammophos at a dose of 100 kg/ha (N12P52) (production control); III, IV, and V – pre-sowing application of sulfoammonium phosphate at a dose of 100 kg/ha (N20P20S14) in combination with post-sowing application of MACROSTAR complex fertilizer at doses of 100 kg/ha, 150 and 200 kg/ha (N9P20K12, N14P30K18 and N18P40K24), respectively. The area of the second-order sowing and accounting plots was 210 and 112 m2, respectively.Research results. Analysis of plant productivity and plant density before harvesting the SY Fenomeno sunflower hybrid revealed their significant dependence on the studied variants of pre-sowing, sowing, and root fertilization.On average, sunflower baskets produced the highest number of seeds in the variant with the highest dose of root application of UAN32 – 125 kg/ha (N40) against the background of pre-sowing application of sulfoamophos at a dose of 100 kg/ha N20P20S14 and post-sowing application of MACROSTAR complex fertilizer at a dose of 200 kg/ha (N18P40K24) – 1257 pcs. Compared to the absolute control (without fertilizer application), the number of seeds in this variant was 224 pcs. or almost 22.0 % higher.The highest seed weight per sunflower basket – 82.8 g – was also observed in the variant with the highest doses of various types of fertilizer application. At the same time, the difference compared to the variant with a lower dose of MACROSTAR complex fertilizer application – 150 kg/ha (N14P30K18) was insignificant – less than 2.0 %.In terms of biological seed yield, the optimal option was pre-sowing application of ammonium sulfate at a dose of 100 kg/ha (N21S24), followed by the application of ammophos at a dose of 100 kg/ha (N12P52) and root application of UAN32 at a dose of     125 kg/ha (N40). Other options for pre-sowing and top dressing with complex fertilizers did not provide a significant increase in the biological yield of sunflower seeds compared to this option (there was only a tendency towards an increase). In addition, the cost of the complex fertilizer MAKROSTAR, as well as sulfoammonium phosphate, per 1 ha was significantly higher than that of ammonium sulfate and ammonium phosphate. Increasing the dose of root application of UAN32 from 95 to 125 kg/ha did not provide a significant increase in the biological yield of sunflower seeds, but there was a clear tendency towards its increase in the variants of root application of a higher dose of UAN32.Conclusions. Thus, this particular feeding system option – pre-sowing application of ammonium sulfate at a dose of 100 kg/ha (N21S24), top dressing with ammophos at a dose of 100 kg/ha (N12P52) in combination with root feeding of crops with UAN32 at a dose of 125 kg/ha (N40), was the best in terms of plant productivity and biological yield of sunflower seeds, both on average over the years and directly by year.
Keywords: sunflower; hybrid; nutrition system; complex fertilizers; productivity elements; pre-sowing and post-sowing application; root feeding; biological seed yield